Euro Area Policies : Staff Report for the 2012 Article IV Consultation with Member Countries. (IMF Staff Country Reports; Country Report ;, 2012)
The 2012 Article IV Consultation report on euro area policies highlights that investors are withholding funding from member states most in need, moving capital 'north' and abroad to perceived safer assets. Executive Directors have noted that the euro area continues to face a number of economic challenges amid increasing financial stresses and market fragmentation. Directors have also stressed that it is important that policymakers continue to demonstrate shared and unequivocal commitment-with a clear, credible roadmap-to a deeper integration of the euro area.